The ayatollahs' democracy : an iranian challenge - Majd, Hooman ([S.l.] : Allen Lane, 2011)
"There are several peculiar features about writing any detailed account of the recent political events in Persia which make necessary some slight explanation. The first point is that Persian political affairs, fraught as they are with misfortune and misery for millions of innocent people, are conducted very much as a well-staged drama - I have heard some critics say, as an opera bouffe". (William Morgan Shuster, "The Strangling of Persia", 1912). So Hooman Majd introduces his story of Iran, with its volatile politics, jostling leaders, global ambitions, and enormous implications for world peace. What does it mean for the world if "Green" represents not a revolution but a civil rights movement, pushing the country toward a particular brand of "Islamic democracy"? And how will Iran's diversity of political positions, so often sidelined in news reporting, ultimately resolve itself? With witty, candid, and stylishly-intelligent reporting, Hooman Majd introduces top-level politicians and clerics alongside regular Iranians, including Jewish community leaders. A personal, candid tour of the political and social landscape in Iran, "The Ayatollahs' Democracy" is a powerful dispatch from a country at a historic turning point.